2022
DOI: 10.3389/fnagi.2022.834765
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Reserve and Related Constructs: A Unified Framework Across Cognitive and Brain Dimensions of Aging

Abstract: Cognitive reserve and related constructs are valuable for aging-related research, but consistency and clarification of terms is needed as there is still no universally agreed upon nomenclature. We propose a new set of definitions for the concepts of reserve, maintenance, and resilience, and we invoke parallel concepts for each that are applicable to cognition and to brain. Our definitions of reserve and resilience correspond reasonably well to dictionary definitions of these terms. We demonstrate logical/metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…A healthy lifestyle that includes cognitive, social, and physical activities was positively correlated with global cognition 18 , which was achieved through informal learning programs and activities such as the University of the Third Age (U3A) 19 . The combination of positive life experiences such as education and participation in cognitive and socially stimulating leisure activities is thought to increase the effectiveness of cognitive processing in aging individuals, also referred to as cognitive reserve (CR) 20 . It improves cognitive function in healthy aging subjects; in particular, CR has been associated with global cognition 21 and has been reported to enhance executive function and attention 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…A healthy lifestyle that includes cognitive, social, and physical activities was positively correlated with global cognition 18 , which was achieved through informal learning programs and activities such as the University of the Third Age (U3A) 19 . The combination of positive life experiences such as education and participation in cognitive and socially stimulating leisure activities is thought to increase the effectiveness of cognitive processing in aging individuals, also referred to as cognitive reserve (CR) 20 . It improves cognitive function in healthy aging subjects; in particular, CR has been associated with global cognition 21 and has been reported to enhance executive function and attention 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…CR can be metaphorically envisioned as software that executes computations in the brain and is shaped by diverse aspects of life experience [12]. This means that cognitive engagement, social interaction, and physical exercise throughout life can all contribute to building and maintaining CR, BM [13], and CM [14].…”
Section: Introductionmentioning
confidence: 99%
“…Cabeza et al [15] highlighted the clear relationship between reserve and maintenance but emphasized their distinct features: reserve enhances and augments resources, while maintenance preserves these resources through constant recovery and repair. Kremen et al [14] suggested that reserve and maintenance are two parallel concepts, and the lack of reference to CM is due to the common use of static CR proxies, such as education, which do not allow for the examination of changes in CR. To promote more consistent and rigorous research, the reserve, resilience, and protective factors professional interest area, established under the auspices of the Alzheimer's Association, formed a white paper workgroup to develop consensus definitions for BR, CR, and BM [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains unclear whether a reverse association is established. A perspective acknowledges that individuals with higher cognitive reserves may be more likely to actively seek out and participate in activities that stimulate their cognitive abilities ( Kremen et al, 2022 ). Moreover, some studies have indirectly suggested that cognitive functioning might impact on cognitive reserve ( Aartsen et al, 2002 ; Jones et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%